Are maximum respiratory pressures predictors of sarcopenia in the elderly? - Pedreira,Rhaine Borges Santos (2022)
ABSTRACT Objective: To compare maximum respiratory pressures and spirometric parameters among elderly individuals classified as having no sarcopenia, probable sarcopenia, and confirmed sarcopenia, and to test the ability of these variables to discriminate sarcopenia in a community-dwelling elderly population. Methods: This was a cross-sectional study involving 221 elderly (≥ 60 years of age) individuals of both sexes. Sarcopenia was diagnosed in accordance with the new consensus of the European Working Group on Sarcopenia in Older People. Maximum respiratory pressures and spirometry parameters were assessed. Results: The prevalences of probable sarcopenia and confirmed sarcopenia were 20.4% and 4.1%, respectively. Regardless of the sex, those with confirmed sarcopenia had significantly lower MEP than those with no sarcopenia and probable sarcopenia, whereas only males with confirmed sarcopenia presented with significantly lower MIP than did the other individuals. There was an inverse association of MIP and MEP with sarcopenia, indicating that the decrease by 1 cmH2O in these parameters increases the chance of sarcopenia by 8% and 7%, respectively. Spirometric parameters were not associated with sarcopenia. Cutoff points for MIP and MEP, respectively, were ≤ 46 cmH2O and ≤ 50 cmH2O for elderly women, whereas they were ≤ 63 cmH2O and ≤ 92 cmH2O for elderly men, and both were identified as predictors of sarcopenia (area under the ROC curve > 0.70). Conclusions: Sarcopenia was associated with lower maximum respiratory pressures, but not with spirometric parameters. Maximum respiratory pressures can be used as markers of sarcopenia in a community-dwelling elderly population regardless of the sex.